Methodology for Determining Time Intervals by Video Recordings - A. G. Boyarov; O. O. Vlasov; I. S. Siparov (Теория и практика судебной экспертизы, 2022)
Video recording as a product of informational and communication technologies has a specific place in the development of the society. The problem of forensic analysis of video recordings has a long history and transforms along with the development of technical means. Video recordings are a valuable source of factual data on cases involving traffic accidents, when in addition to describing the contentrelated side of the case, it is necessary to make certain calculations of temporal and spatial characteristics.The paper aims to form a unified methodological approach to establishing the temporal characteristics of events recorded on a video as part of forensic analysis of video footage. The authors present a framework for selecting a correct source of data when determining time intervals, describe a step-by-step sequence of actions for an expert to solve the question put to him, and the methods to determine time intervals.